The impact of industry concentration on the market's ability to anticipate future earnings: International evidence. Issue 4 (3rd October 2016) - Haw, In-Mu; Hu, Bingbing; Lee, Jay Junghun; Wu, Woody
Abstract : Purpose: The existing literature has established the importance of industry concentration in explaining firm performance and information environments. However, little is known about whether and how industry concentration affects investors' ability to anticipate future earnings. This paper aims to investigate this query by identifying and testing two channels, product market power and intra-industry information transfer, through which industry concentration affects the informativeness of stock returns about future earnings. Design/methodology/approach: The paper measures the informativeness of stock returns about future earnings by the future earnings response coefficient (FERC)). This study estimates the FERC using a firm-level sample from 38 economies. Findings: The authors find that industry concentration significantly enhances investors' ability to predict future earnings. Further tests show that both product market power and intra-industry information transfer contribute to explaining the positive association between industry concentration and the FERC, with the former playing a more salient role. Finally, the authors show that a country's effective competition law attenuates the positive impact of industry concentration on the FERC by weakening the economic impact of the two underlying channels. Originality/value: This study contributes to the growing literature on the price-leading-earnings relation, industry concentration and international corporate governance.